The repression of smudge perpetrated by police in congolese law - Emmanuel Imbwatcheke Bofonga; Jean Losumbe Bondondo (IJRDO - Journal of Social Science and Humanities Research, 2019)
In Democratic Republic of Congo (DRC), citizens worry about persistence or recrudescence of smudge phenomenon. While at juridical or theoritical level, the Congolese National Police (CNP) is among monitored and controlled public services by internal and external juridical texts. However, on the institutional level, the police internal control is by three organes : The General Inspection of Police represented in provinces by Provincial Antena, A special unity called "Police of Police" and Hierarchic control performed by commanders affected in different specilized unities and other constituency corps of police. The weaknesses of internal control which render extermely opacity in doubtet process of police repression which facililates an external control of police. Therefore, on external side, the CNP is firstly controlled by juridical institution : Officer of Public Minister, the administrative juridictions and military juridictions. In addition, this research paper attemps to analyze other types of external police controls, known by the DRC Constitution, which suscptible organizational strength affects positily on the process of smudge repression. There are political, social and friendly controls. Nevertheless, with regard to the great phenomenon of smudge of police in DRC, it is mandatory to sensitize the citizens on these diferent mecanisms quoted above which are meant to lead to repression of police smudge.